Islam-West Interaction in the Modern Era : Historical Dynamics, Contemporary Challenges, and Future Prospects - Abdul Husain Natsir; St Halimang (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the complex dynamics of Islam-West interactions through a historical-analytical approach, focusing on the evolution of these relations from medieval encounters to contemporary developments. Using qualitative methods through extensive literature review and critical discourse analysis, this study analyzes the multifaceted nature of Islam-West relations across historical periods, contemporary contexts, and emerging paradigms of engagement. Findings reveal that Islam-West interactions have evolved through distinct historical phases: medieval encounters characterized by both intellectual exchange and military conflicts, colonial experiences that created lasting power asymmetries, and contemporary dynamics shaped by geopolitical tensions, migration patterns, and globalization. The research identifies three major contemporary challenges: persistent Orientalist and Islamophobic discourses, geopolitical conflicts intensifying civilizational narratives, and internal diversity within both civilizational spheres that complicates unified engagement. The study proposes a transformative model of Islam-West relations founded on shared ethical values, contextual understanding of religious texts, collaborative approaches to global challenges, and recognition of internal pluralism within both traditions. This research contributes to intercultural understanding by offering a nuanced historical perspective on Islam-West relations and establishing a theoretical framework for constructive engagement in an increasingly interconnected world